International Business in Australia before World War One Shaping a Multinational Economy - Ville, Simon; Merrett, David (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2022)
"This ambitious study reshapes our understanding of the history and impact of multinational firms in Australia, and skillfully weaves the local story into a global framework." - Professor Geoff Jones, Harvard Business School "Simon Ville and David Merrett in this pioneering study show that on the eve of World War I (1914) a sizable collection of multinational enterprises, principally from the UK, with the US in second place, from a number of continental European nations (and in addition from Canada, New Zealand and Japan and other locales) had an Australian presence, beyond independent agents; the multinationals operated in many diverse sectors of the Australian economy. The authors survey the large existing literature on the course of nineteenth and early twentieth century foreign investment in Australia and conclude that before 1914 the multinational firms that they identified, counted, and classified had an important impact on Australian economic development." - Professor Mira Wilkins, Florida International University This book challenges conventional wisdom by revealing an extensive and heterogeneous community of foreign businesses in Australia before 1914. Multinational enterprise arrived predominantly from Britain, but other sender nations included the USA, France, Germany, New Zealand, and Japan. Their firms spread out across Australia from mining and pastoral communities, to portside industries and CBD precincts, and they operated broadly across mining, trading, shipping, insurance, finance, and manufacturing. They were a remarkably diverse population of firms by size, organisational form, and longevity. This is a rare study of the impact of multinationals on a host nation, particularly before World War One, and that focuses on a successful resource-based economy. Deploying a database of more than 600 firms, supported by contemporary archives and publications, the work reveals how multinational influence was contested by domestic enterprise, other foreign firms, and the strategic investments of governments in network industries. Nonetheless, foreign agency - particularly investment, knowledge and entrepreneurship - mattered in the economic development of Australia in the nineteenth as well as the twentieth centuries. This book will be of interest to students and researchers in Australian and international economic and business history, the history of economic growth and scholars of international business. Simon Ville is Senior Professor of Economic and Business History and Associate Dean Research at the University of Wollongong, Australia. He is a Fellow of the Academy of Social Sciences in Australia and will be the Whitlam-Fraser Professor of Australian Studies at Harvard University in 2022-3. He has written widely on big business, foreign investment, the rural and resource industries, the natural history trade, social capital, transport history, and the Vietnam War. David Merrett is a Professor Emeritus at the University of Melbourne. He has published widely in Australian economic and business history. His current interests include the rise of big business and the internationalisation of the Australian economy in the twentieth century. He has numerous publications on foreign firms in Australia, notably ANZ Bank (1985), but also on Australian firms as multinationals. .
Chapter 1: The international connections of the Australian colonies -- Chapter 2: Foreign investment before World War One -- Chapter 3: Hidden from view. The multinational enterprise in colonial Australia -- Chapter 4: Early entrants: MNEs in Australia, c.1820-70 -- Chapter 5: The Spread of the Multinational Economy by 1914 -- Chapter 6: Why did they come? -- Chapter 7: Where did they go? Multinationals and the development of Australia -- Chapter 8: Global Hosts -- Chapter 9: Distance no Tyranny.
Keywords: Economic history; International business enterprises; Imperialism; International finance; Economic development; Economic History; International Business; Imperialism and Colonialism; International Finance; Economic Growth